Effect of sales promotion costs Yamaha motorcycle brand in Scorpio CV. Jadi Cemerlang Jaya Pekanbaru - Andi Rikson; Jushermi '; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is conducted to determine the effect of Promotion Cost (CostAdvertising, Sales Promotion Costs, and Cost Personal Selling) Motorcycles for Sale Yamaha Scorpio Brands at CV. Jadi Cemerlang Jaya Pekanbaru and promotion costs to determine which is the most dominant effect on the Yamaha Motorcycle Sales BrandScorpio at CV. Jadi Cemerlang Jaya Pekanbaru. To analyze the data, in this study used linear regression test is to prove the direction of the influence of service as an independent variable (X1) Price as an independent variable (X2) Sales as the dependent variable (Y) then used multiple linear regression equation.The results showed that simultaneous advertising, sales promotion and personal selling influence sales on the CV. Jadi Cemerlang Jaya Pekanbaru. While partially variable costs Cost Advertising and personal selling to sales in the CV. Jadi Cemerlang Jaya Pekanbaru. While sales promotion costs have no effect on sales. Based on the calculation of the R value of 0.628, meaning the closeness of the relationship jointly between the dependent variable and the independent variables strongly as R> 0.5. R2 value (coefficient of determination) of 0.395 means that 39.50% rate of sales of Yamaha motorcycles socpio type of CV. Jadi Cemerlang Jaya Pekanbaru be affected by Cost Advertising, sales promotion. A percentage of 63.10% is influenced by other variables not included in this studyKeyword : Campaign Costs (Cost Advertising, Sales Promotion Costs, and Cost Personal Selling) to Sales